THE METHODICAL ASPECTS OF DISTANCE LEARNING FOR ART’S EDUCATIONAL PROGRAMMES - Zhanguzhinova, Meruyert; Karzhaubaeva, Sangul; Khalykov, Kabyl; Zhanbirshiev, Orynbasar; Koesov, Timur (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article discusses the problem of methodical aspects integration in distance learning for Art’s educational programmes in Higher Educational Institutions (HEI). The relevance of research reflects the quarantine measures for the non-proliferation of coronavirus infection Covid19 in Art's universities of Kazakhstan in current state of distance learning. The novelty of the research is the implementation of educational policy according to the Kazakhstani state program within the conditions of distance learning. The aim of research is to reveal the methodological aspects for training Art students within distance learning in accordance with the topical problems in education, based on the new technologies and methods of digitalization. Primary methods of research are based on Case studies, which include theoretical review of the practical application of the MOODLE platform into distance learning. The result of the research is disclosure of the experience of the Art’s teachers in conducting the study process within the framework of distance learning technologies (DLT). The research illustrates the example of study process of the Department of Scenography of T. K. Zhurgenov Kazakh National Academy of Arts based on the bachelor educational programs: Stage decoration, Multimedia scenography, Film and TV director, Stage costume, Theatrical makeup.